Pentingnya Akreditasi Rumah Sakit Bagi Pelayanan Kesehatan: Hospital Application Study - Hadiansyah Hadiansyah; Dety Mulyanti (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Hospitals in guaranteeing good service quality and patient safety must be proven through accreditation. Accreditation is carried out by submitting an application to the Hospital Accreditation Commission (KARS). Hospital Accreditation is a way of monitoring the implementation of measuring hospital performance indicators. The purpose of writing this scientific article is to find out the importance of improving the quality of hospitals, especially for hospital structures and health workers. The method in this scientific article is to compare cases from several hospital studies that apply the accreditation process and the literature collected at the editing (re-examination) stage. The data is then processed and analyzed and conclusions drawn. The findings from the study of the application of hospitals in the importance of holding accreditation are to improve the quality of hospital services, improve hospital patient safety, increase protection for patients, the public, human resources for hospitals and hospitals as institutions and support government programs in the health sector. It can be concluded that the importance of hospitals carrying out accreditation is to ensure good service quality and patient safety must be proven through accreditation. Accreditation is carried out by submitting an application to the Hospital Accreditation Commission (KARS). Suggestions made for hospital agencies, namely hospitals that have obtained national accreditation status are required to make strategic improvement plans in accordance with the surveyor's recommendations to meet hospital service standards that have not been achieved.